Atorvastatin Induced Vasculitis - T, Prasad; V, Kalaiselvan; S, Surabhi; D, Vivek; S, Ranvirkumar; S, Gyanendra Nath (Indian Journal of Pharmacy Practice)
Adverse drug reactions are regarded as an important public health problem as they may be potentially life- threatening. The World Health Organization defines Adverse drug reaction (Adverse Drug Reaction) as a response to a drug which is noxious, unintended, which occurs at doses normally used in human for prophylaxis or diagnosis of a disease or for modification of physiological function. We report two adverse drug reaction case reports. Case 1: A forty six years old Indian female adult developed Vasculitis over both legs and back after four months. Patient was prescribed Tablet Atorvastatin 20 mg, Tablet Atenolol 25 mg, Tablet Levothyroxine sodium 100 mg and Tablet Acetylsalicylic acid 100 mg. Patient had been treated with methylprednisolone and azathioprine. Case 2: A fifty six years old Indian female adult had been treated with Atorvastatin 10 mg, Telmisartan 40 mg and Zolpidem 10 mg for essential hypertension. Patient had been treated with methylprednisolone. Hence there is a need for awareness of the adverse events related to statins therapy to avoid life-threatening complications.
Keywords: Pharmacovigilance; Adverse Drug Reaction; Atorvastatin; Vasculitis; Suspected Unexpected Serious ADR (SUSAR)